Indo-Muslim Interactions in the Mojaddedi Tradition: Observations on ʿAndalib’s Nāla-ye ʿAndalib - Khodamoradi, Soraya (Journal of Persianate studies, 2024)
Sufism in South Asia has enjoyed a rich heritage of interactions with Indian cultures, religions, and learned traditions. Sufis have continuously exchanged ideas and practices with adherents of Indian religions, as well as reactionary trends opposing such discourse. The reformist Sufi Mojaddediyya (“Renewal”) movement, founded by Ahmad Serhendi (1564–1624), with its call for a return to a pure Islam, is a remarkable example of such anti-hybridization dynamics. “Pure” refers, among other meanings, to a kind of Islam that is stripped of religious innovation (bedʿa), including non-Muslim traditions, beliefs, and social and moral norms adopted by Muslims. By means of textual and intertextual analysis, this article tries to shed light on the position of the Mojaddedi “pure Mohammadi way (tariqa Mohammadiyya khālesa)” towards Indo-Persian and Indo-Muslim interactions. For this purpose, we shall examine closely the Nāla-ye ʿAndalib (The Nightingale’s Lament), the Persian masterpiece by the founder of this path, Mohammad Nāser ʿAndalib (1693/4–1759).